The Influence of Financial Stress on The Financial WellBeing Among Team Leaders - C. Sobrejuanite, Glenndon; M. Villanueva, Donna Grace; M. Mandin, Kristine Danielle; F. Doromal, Bea Wonderful (International Journal of Management and Education in Human Development, 2024)
This study investigates the influence of financial stress on the financial well-being among the respondents in Davao City's business process outsourcing (BPO) organizations, the team leaders. The research was conducted in the four BPO companies in Davao City with a total number of one hundred respondents. This research used a simple random sampling technique in selecting research respondents as well as a validated questionnaire to conduct a study. The adopted questionnaire contained financial stress and financial well-being assessment. The study results revealed that respondents had a reasonably average level of financial stress and an average level of financial well-being as well. These associations imply that as the amount of financial stress rises, so will the negative level of affective reaction, relational behavior, and physiological response. The results suggest that as financial stress levels increase, negative financial well-being tends to increase as well, and vice versa. A positive correlation implies that an increase negative effect on financial well-being increases financial stress, anxiety levels, and diminish job performance. Overall, the study's insights emphasize the importance of addressing financial stress among team leaders and tailoring interventions to improve their financial well-being.